Estratégias de sobressemeadura de forrageiras em soja para produção de forragens outonal, persistência da palhada e densidades de plantas daninhas em trigo - Manfron, Angelica Consoladora Andrade (2022)
The off-season period between the harvest of the summer crop and the sowing of the winter crop is little used by farmers, generating problems such as the increase of weeds in the area, not to mention that it is a critical period for the production of forage used. in animal feed, and can be better used. Thus, the general objective of this thesis was to evaluate whether forage sowing strategies in the off-season alter weed density, forage production and soil cover persistence. For this, two experiments were carried out in the experimental fields of Embrapa Trigo, in the municipality of Coxilha (RS) in 2019, and of Passo Fundo (RS) in 2020. The first experiment is described in chapter I where two soybeans were sown after the soybean harvest. cultivars of dual-purpose wheat (BRS Tarumã and BRS Pastoreio), three of rye (BRS Serrano, BRS Progresso and Temprano), three of black oat (Embrapa 139 Neblina, BRS Madrugada and BRS Centauro), one of millet (BRS 1503) and one of Sudan grass (BRS Estribo), a mixture of Sudan grass + Dual purpose wheat (BRS Estribo + Grazing), Sudan grass + Black oat (BRS Estribo + Embrapa 139) and fallow. In the second experiment, described in Chapter II, the same forages were oversown in soybean, thus altering the forage sowing strategy in the off-season. For both experiments, a randomized block design was used, in three replications, for two years, which were also considered as a factor. In general, aspects such as the initial stand of forage plants, dry mass production and its behavior as residue, since its persistence in the soil, were evaluated in the two experiments, as well as its influence on the yield components of the subsequent crop, which for both cases was the wheat. We realized with this work the great influence of weather conditions on each sowing strategy used, showing that the overseeding technique provides higher forage values for animal production than when the forages are sown after the soybean crop, but its straw does not decrease. weed density and does not change wheat yield components. As well, none of the forages studied in the two sowing strategies had changes in the persistence of soil cover for the subsequent crop.